2018
DOI: 10.5194/bg-2018-295
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Weaving of biomineralization framework in rotaliid foraminifera: Implications for paleoenvironmental reconstructions

Abstract: Abstract. Foraminifera are commonly used to reconstruct paleoenvironmental conditions based on the taxonomical composition, as well as elemental and/or isotopic signatures of their calcareous tests. A major problem, often referred to as the 'vital effect', is that such geochemical signatures stored in inorganic calcium carbonates differ greatly under the same environmental conditions. This effect was previously explained by proportional contributions from passive vs active ion 5 transport patterns, but their d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…This interpretation agrees with observations of membrane probes labeling thin ectoplasmic layer that most likely isolated the crystals from the surrounding water during mineralization ( 32 ). Recent ultrastructural SEM investigations also document another globothalamean species ( Ammonia ) that revealed isolation of calcification sites by two external organic layers, i.e., inner and outer organic layers, entrapping the POS ( 41 , 42 ). These external layers, actively involved in calcification during the chamber formation, truly represent inner and outer lamellipodial structures identified in A. lessonii .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This interpretation agrees with observations of membrane probes labeling thin ectoplasmic layer that most likely isolated the crystals from the surrounding water during mineralization ( 32 ). Recent ultrastructural SEM investigations also document another globothalamean species ( Ammonia ) that revealed isolation of calcification sites by two external organic layers, i.e., inner and outer organic layers, entrapping the POS ( 41 , 42 ). These external layers, actively involved in calcification during the chamber formation, truly represent inner and outer lamellipodial structures identified in A. lessonii .…”
Section: Discussionmentioning
confidence: 89%
“…These external layers, actively involved in calcification during the chamber formation, truly represent inner and outer lamellipodial structures identified in A. lessonii . Authors suggest an early “leakage” of seawater through tiny holes of outer/inner organic layers at the onset of mineralization ( 42 ). Further research is required to investigate this phenomenon and its consequences.…”
Section: Discussionmentioning
confidence: 99%
“…leakage, initial seawater enclosed at the site of calcification or seawater endocytosis), while SO 4 2would not be transported by the Cachannels or -pumps. Only prior to or at the first stages of chamber formation, when the membrane is perhaps not fully closed (Nagai et al, 2018) and the fluid in the site of calcification (SOC) resembles seawater, SO 4 2is incorporated due to the relatively Biogeosciences Discuss., https://doi.org/10.5194/bg-2018-481 Manuscript under review for journal Biogeosciences Discussion started: 12 December 2018 c Author(s) 2018. CC BY 4.0 License.…”
Section: Element Transport During Biomineralizationmentioning
confidence: 99%
“…In perforate hyaline species, studies have shown that the site of calcification is separated from the surrounding seawater by a protective envelope. Although observations for Ammonia suggest this envelope might not be closed at the start of calcification (Nagai et al, 2018), the carbonate chemistry at the site of calcification is proposed to be controlled by the foraminifer and e.g. characterized by a high internal and low external pH Toyofuku et al, 2017), as well as the chemistry of the calcification fluid itself .…”
Section: Introductionmentioning
confidence: 99%